2015
DOI: 10.1007/s12205-015-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the effect of blast-induced vibration from adjacent tunnel on existing tunnel

Abstract: Since the new tunnel is close to existing tunnel, the vibration wave induced by blasting endangers the safety and stabilization of the surrounding rock and the lining of existing tunnel. In the tunnel blasting vibration monitoring and safety prediction, Peak Particle Velocity (PPV) and vibration frequency are used widely as safety standards. To investigate the effect of blast-induced vibration from adjacent tunnel on existing tunnel, field monitoring experiments and a numerical method that is Finite Element Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…To compare numerical simulation results with the field measurement results, as well as to more fully understand the vibration characteristic of the tower main frame under the blasting, a three-dimensional finite element model was established by Midas-GTS finite element software, which was generally used to conduct the geotechnical analysis. Based on St. Venant principle [49,50], it is appropriate to take three times of the size of tunnel face for left, right, and bottom parts of the model to reduce the influence of boundary effects. So, the model size is 150 m × 120 m × 90 m, as shown in Figure 12.…”
Section: Numerical Simulation and Analysismentioning
confidence: 99%
“…To compare numerical simulation results with the field measurement results, as well as to more fully understand the vibration characteristic of the tower main frame under the blasting, a three-dimensional finite element model was established by Midas-GTS finite element software, which was generally used to conduct the geotechnical analysis. Based on St. Venant principle [49,50], it is appropriate to take three times of the size of tunnel face for left, right, and bottom parts of the model to reduce the influence of boundary effects. So, the model size is 150 m × 120 m × 90 m, as shown in Figure 12.…”
Section: Numerical Simulation and Analysismentioning
confidence: 99%
“…In recent decade, numerical modeling has been introduced to check the stability. When the tunnel has been made, stability is an important factor due to advancing cycle and cost especially in soil or weak rock [2].…”
Section: Introductionmentioning
confidence: 99%
“…The main conclusions are: (1) on the stepped portion of the hole excavation on the scope of the maximum slope excavation slope deformation rate in step fastest, over time, the deformation gradually converge. (2) along the longitudinal direction of the tunnel, the more monitoring points away from the hole excavation unit distance, the smaller the amount of deformation of the slope obtained its monitoring. (3) by Yang slope settling cloud contrast slope under different cavity length of the inner body can be seen: With the entry of the mountain tunnel and increase the body, affecting Yang slope deformation area also increased to reflect the slope according to the monitoring point.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [13] summarized the tectonic structure, geomorphology, hydrogeology, and engineering geology in Guangzhou, China, and reported a collapse of the tunnel face resulting from a blast operation in construction of Guangzhou Subway, which led to a serious sinkhole of 690 m 2 , and the collapse of two buildings. Actually, many drill-and-blast practices have been conducted during hydraulic tunnels or mining shafts [14][15][16][17][18][19], which indicated that blasting vibration has critical influence on damage or failure of surrounding rock mass and lining.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [19] adopted a Finite Element Method (FEM) to study blasting vibration velocity and vibration frequency on existing tunnel. Result shows that field monitoring experiment and numerical simulation can optimize blasting excavation program and provide a reference for other similar engineering projects.…”
Section: Introductionmentioning
confidence: 99%